The effect of different surface conditioning methods and curing protocols on bond strengths of two different fissure sealants - Sezin Özer; Nihan Gönülol; Emine Şen Tunç; Tuba Ay (Gazi University, 2016)
OBJECTIVE: To evaluate in vitro shear bond strength of two different resin-based fissure sealants [BeautiSealant (BS), UltraSeal XT hydro (UH)] associated with application of an acid etching (Ultra-Etch Acid) or a primer (BeautiSealant Primer) and two different polymerization modes (Standard mode; 10 s or Xtra power mode; 3 s) of a third generation light emitting diode (LED) light curing unit. MATERIALS AND METHOD: Eighty enamel surface samples were prepared from 40 extracted human third molar teeth. Samples were randomly divided into 8 subgroups according to fissure sealants, conditioning methods and polymerization modes (n=10); Group 1: Acid + BS+ Xtra power mode, Group 2: Primer + BS + Xtra power mode, Group 3: Acid + BS + Standard mode, Group 4: Primer + BS + Standard mode, Group 5: Acid + UH + Xtra power mode, Group 6: Primer + UH + Xtra power mode, Group 7: Acid + UH + Standard mode, Group 8: Primer + UH + Standard mode. An Instron machine (1.0 mm/min) was used to measure shear bond strength values. Data were statistically analyzed by using one-way ANOVA and Tukey's test (p<0.05). RESULTS: Significant differences were detected between the groups (p<0.05). Shear bond strength values of all BS subgroups were significantly lower than UH subgroups (p<0.05). Highest shear bond strength values were obtained in Group 5 and the lowest was obtained in Group 1. CONCLUSION: Shear bond strength values of fissure sealants can be affected by surface conditioning methods and curing protocols.